The Quality of Life Related to Oral Health Among The Elderly Based on Pathological Lesions in Soft Tissues - Nurfianti Nurfianti; Putri Ayu Nurhadizah; Ahmad Ronal; Audiawati Audiawati; Siti Nur Riani; Faezah Rokhani; Aspalilah Alias (Public Health Undergraduate Program, Faculty of Health Science, Universitas Pembangunan Nasional Veteran Jakarta, 2025)
Background: Oral health plays an important role in overall health and quality of life among the elderly. The presence of soft tissue lesions in the oral cavity, particularly in this vulnerable population, warrants attention due to its potential association with systemic health conditions and overall quality of life. Maintaining a high quality of life is crucial, as it is closely linked to health status, life satisfaction, and overall well-being. This study aimed to examine oral health–related quality of life among the elderly, with particular focus on the presence of pathological soft tissue lesions. Method: A cross-sectional study was conducted using a purposive sampling technique. Data collection included demographic information, administration of the Oral Health Impact Profile (OHIP-14) questionnaire, and comprehensive intraoral examinations to identify pathological lesions. The Mann–Whitney U test was used to compare quality-of-life scores between elderly individuals with and without pathological lesions. Results: Among the 94 subjects examined, 36 were found to have pathological lesions, while none of the 58 (p=0.024, p<0.05) showed a difference in the quality of life between elderly individuals with and without pathological lesions. Conclusion: There is a significant difference in oral health–related quality of life among the elderly, which is influenced by the presence of pathological soft tissue lesions.